Nursing informatics competency and its associated factors among palliative care nurses: an online survey in mainland China - Junchen Guo; Junqingzhao Liu; Chaoyi Liu; Ying Wang; Xianghua Xu; Yongyi Chen (BMC, 2024)
Abstract Background Nursing informatics (NI) competency is a required core competency for high-quality care in digitally enabled healthcare environments. Given the increasing reliance on digital health in palliative care settings, it becomes crucial to evaluate the NI competency of nurses to ensure the seamless integration and effective utilization of digital health in their clinical practice. This study aimed to investigate the level of NI competency and explore its associated factors among palliative care nurses in mainland China. Methods A cross-sectional design was conducted for this study, involving a total of 409 palliative care nurses from 302 hospitals in mainland China. Anonymous data were collected through a self-designed sociodemographic questionnaire, the Nursing Informatics Competency Scale (NICS) and the Innovative Self-Efficacy Scale. Results The total score of the NICS was 129.19 ± 22.02, which indicated that Chinese palliative care nurses had a moderate level of NI competency. There was a positive correlation between innovative self-efficacy and NI competency (r = 0.602, P < 0.01). The hospital level and innovative self-efficacy were identified as statistically significant factors influencing nurses' NI competency based on multiple linear regression analysis results. These associated factors could explain 35.1% of the difference in NI competency. Conclusions This study found that palliative care nurses in mainland China exhibited moderate levels of NI competency and identified the hospital level and innovative self-efficacy as associated factors of nurses' NI competency. Measures such as developing supported strategies, including targeted NI training programs by nursing education managers of primary-level hospitals and creating a positive culture of innovation by healthcare institutions can be considered to improve the level of NI competency among Chinese palliative care nurses.